2007
DOI: 10.1097/acm.0b013e3180555a2d
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Cultural Competence: Examining Hidden Assumptions

Abstract: Existing measures embed highly problematic assumptions about what constitutes cultural competence. They ignore the power relations of social inequality and assume that individual knowledge and self-confidence are sufficient for change. Developing measures that assess cultural humility and/or assess actual practice are needed if educators in the health professions and health professionals are to move forward in efforts to understand, teach, practice, and evaluate cultural competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
212
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(218 citation statements)
references
References 31 publications
5
212
0
1
Order By: Relevance
“…This focus on the individual level is consistent with experience in the US, where cultural competence is a mandated requirement in healthcare. In a systematic review of instruments that seek to measure cultural competence, Kumaş -Tan et al 32 found problematic assumptions about what it is, and a tendency to reduce it to the level of individual knowledge and skills. This focus on the individual, leading to an overemphasis on training, has been noted by others in this field 33 and in international development programs.…”
Section: Discussionmentioning
confidence: 99%
“…This focus on the individual level is consistent with experience in the US, where cultural competence is a mandated requirement in healthcare. In a systematic review of instruments that seek to measure cultural competence, Kumaş -Tan et al 32 found problematic assumptions about what it is, and a tendency to reduce it to the level of individual knowledge and skills. This focus on the individual, leading to an overemphasis on training, has been noted by others in this field 33 and in international development programs.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of the literature, Kumas-Tan et al [5] identified the 10 most commonly used measures in their evaluation of 54 cultural competence measures identified in the literature. These measures included the Multicultural Counseling Inventory; Cultural SelfEfficiency Scale; Inventory for Assessing the Process of Cultural Competence Among Health Professionals; CrossCultural Adaptability Inventory; Quick Discrimination Index; Cultural Attitude Scale; Multicultural Awareness, Knowledge, and Skills Survey; Cultural Competence SelfAssessment Questionnaire; Cross-Cultural Counseling Inventory; and Multicultural Counseling, Knowledge, and Awareness Survey.…”
Section: Methodologies For Evaluating Cccementioning
confidence: 99%
“…1 (Betancourt 2003(Betancourt , 2006Bromley and Braslow 2008;Crenshaw et al 2011;Eiser and Ellis 2007;Fung et al 2008;Green et al 2008;Guarnaccia and Rodriguez 1996;Hayes-Bautista 2003;Hershberger et al 2008; Kirmayer 2011Kirmayer , 2012aKripalani et al 2006;Kumaş-Tan et al 2007;Lié et al 2006;Lim and Lu 2008;Lo and Stacey 2008;Núñez 2000;Park et al 2006;Park et al 2009;Shapiro et al 2006;Smith et al 2007; South-Paul and Like 2008; Sue 1998Sue , 2003Sumpter and Carthon 2011;Teal and Street 2009;Tervalon 2003;Tervalon and Murray-Garcia 1998;Wachtler and Troein 2003;Wear 2003;Whitcomb 2003).…”
Section: Introductionmentioning
confidence: 99%